1997
DOI: 10.1093/bja/78.6.652
|View full text |Cite
|
Sign up to set email alerts
|

Phantom pain and sensation among British veteran amputees

Abstract: Using a mail-delivered questionnaire, we surveyed 590 veteran amputees concerning phantom pain, phantom sensation and stump pain. They were selected randomly from a population of 2974 veterans with long-standing limb amputation(s) using a computer random number generator. Eighty-nine percent responded and of these, 55% reported phantom limb pain and 56% stump pain. There was a strong correlation between phantom pain and phantom sensation. The intensity of phantom sensation was a significant predictor for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
128
0
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(153 citation statements)
references
References 18 publications
11
128
0
14
Order By: Relevance
“…However, 31.3 and 31.6% of BP and RLP patients, respectively reported pain frequency of at least 4 times per week, and 39.2 and 31.6% of BP and RLP patients, respectively, reported pain duration of several hours to days at a time. Similar findings were reported by Wartan et al [5] and Ehde et al [7,9]. We suspect that these patients' pain interference scores are mild and that they feel they can proceed with daily activities, despite the frequency and duration of their pain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, 31.3 and 31.6% of BP and RLP patients, respectively reported pain frequency of at least 4 times per week, and 39.2 and 31.6% of BP and RLP patients, respectively, reported pain duration of several hours to days at a time. Similar findings were reported by Wartan et al [5] and Ehde et al [7,9]. We suspect that these patients' pain interference scores are mild and that they feel they can proceed with daily activities, despite the frequency and duration of their pain.…”
Section: Discussionsupporting
confidence: 88%
“…[2][3][4][5][6][7][8][9][10] We found that in the majority of cases, BP and RLP are intermittent, of low frequency (not more than 3 times per week) and each episode is of short duration (not greater than 1 h). However, 31.3 and 31.6% of BP and RLP patients, respectively reported pain frequency of at least 4 times per week, and 39.2 and 31.6% of BP and RLP patients, respectively, reported pain duration of several hours to days at a time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of standardized diagnostic criteria not only prevents the identification of causative mechanisms of these types of pains, but also makes it difficult for researchers to accurately assess chronic pain incidence in limp amputees. In a survey of a large population of war veteran amputees, 55% of veteran amputees reported sustained phantom limb pain and 56% reported residual limb pain [1]. Similarly, interviews with 914 limbamputees by telephone revealed that phantom limb pain was experienced by 79.9%, and residual limb pain by 67.7% of the amputees [2].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was (1) to evaluate the relationship between pain and depressive mood amongst community dwelling individuals with limb amputations using established scoring tools, and (2) to examine the relationship between the etiology (work-related trauma or other types of etiology) of amputation and depressive mood.…”
Section: Introductionmentioning
confidence: 99%